Empowered teams : case-study analyses of the process of introducing empowered teams into organisations with a poor industrial relations history - Scott-Lennon, Frank (Cranfield University, 2001)
This research focuses on case-study analyses of the process of introducing empowered teams into organisations with a poor industrial relations history. The chosen research methodology is in the ethnographic mode and analogous to grounded theory; data was collected in five case-study organisations. The respondent data is presented for each case study in turn and then analysed in a cross-case manner, highlighting some critical themes/issues identified by respondents who were key to the process of introducing empowered teams into their organisations. Principal among these critical themes/issues were: pre- planning, visioning/directioning, managerial commitment, role clarity, communications, union engagement, skill development and training, reward/money and trust. This researcher interprets the data from within organisations in our chosen context and develops a model aimed at explaining the leadership processes that affect the five critical enabling conditions of shared values, key processes, role clarity, training and employee-centred systems. The model highlights the critical importance of personal and organisational leadership skills within the organisation to facilitate focus on the above enabling conditions and on the key leadership processes of 'articulation' and 'promulgation'. Suggestions are made for possible lines of future research in terms of either replicating this work or in searching for outcomes with respect to operational and/or opportunity potential within an input-process-output model.